Batch Study for Pesticide Glyphosate Adsorption onto Palm Oil Fronds Activated Carbon - Salman, J.M.; Abid, F.M.; Muhammed, A.A. (Asian Journal of Chemistry, 2012)
The adsorption of glyphosate from aqueous solution onto activated carbon derived from palm oil fronds (PFAC) was investigated through batch study. The effects of both initial concentration and pH of the glyphosat over the range of 25 to 250 mg/L and 2 to 12, respectively on the adsorption of the prepared PFAC were studied in batch experiments. Equilibrium data were fitted to the Langmuir, the Freundlich and the Temkin isotherm models. The results obtained from application of these models show that the best fits were achieved with the Langmuir model and a maximum monolayer adsorption capacity of 104.2 mg/g was obtained at 30 ºC. The regeneration efficiency of spent activated carbon was studied and it was found to be 94.0-96.1 %. The results indicated that PFAC has good capability as adsorbent for the removal of glyphosate from aqueous solutions.